Transverse impact response of hybrid biaxial/uniaxial braided composite tubes. (1st October 2021) - Shi, Lin; Wu, Zhenyu; Cheng, Xiaoying; Pan, Zhongxiang; Yuan, Yanhong
Highlights: The transverse impact response of hybrid biaxial/uniaxial braided tube was studied. The effects of architecture hybridization and stacking sequence were identified. Proposed FE model provided accurate predication of the impact behaviors. Abstract: Tubular composites in automobile engineering are susceptible to transverse loading events. This paper deals with transverse low-velocity impacts on interply hybrid tubes made of biaxial/uniaxial braided fabric layers. For comparison, drop weight tests were performed on hybrid tubes with biaxial braided surface layers and uniaxial braided inner layer (BUB), with contrary stacking sequence (UBU), pure biaxial and uniaxial braided tubes (BBB and UUU). Numerical models were established to predict the impact behaviors and evaluate the hybrid effects. X-ray micro-computed tomography (Micro-CT) was also employed to identity the cracking location and characterize the damage mechanism. The results showed that the impact response of braided tube was related to its structural deformation resistance, which was determined by properties of reinforced layers varying with different stacking sequence. The hybrid effect became more obvious at higher impact energy. At impact energy of 15.4 J, hybrid tube (BUB) yielded the highest impact resistance with small structural deformation. The biaxial braided layer protected the specimen surface by constraining intralaminar crack propagation through the interlacing patterns. Meanwhile, it promoted crack tip propagating to the subsequent uniaxial braided layer and transferred the impact load. Thus, the material involvement of the inner layer was improved, which was responsible for providing a higher in-plane tensile property due to its low yarn crimp.